Vehicular Networks: Embracing Wireless Heterogeneous Communications through Vertical Handover - DA SILVA, LUIZ (My University, 2013)
By taking advantage of the ever growing deployment of wireless networks, the automotive industry is increasingly enabling vehicles to communicate with one another and with the infrastructure, with benefits to information delivery and safety on the road. Vertical Handovers can be used to ensure that the Quality of Service demanded by applications (e.g., throughput, latency) is met while the vehicle is changing its position. In this paper we present a Vertical Handover Decision Algorithm empowered by the IEEE 802.21 standard and its services. Our proposed algorithm uses the vehicle?s on-board unit features and considers the geolocation, the car navigation and a realistic propagation model for heterogeneous underlying networks such as Wi-Fi, WiMAX, and UMTS. Our results demonstrate, through a case of study, that QoS can be guaranteed when location and networking parameters are jointly considered when performing vertical handover.
Actas de la XXIV Jornadas de Paralelismo
PUBLISHED
Madrid, Spain
Keywords: Vehicular Networks; Telecommunications